Doctor Who. Last Christmas [videorecording (DVD)] - Capaldi, Peter; Coleman, Jenna, 1986-; Frost, Nick, 1970- (British Broadcasting Corporation, 2015)
The Twelfth Doctor and his companion are joined by a fan favorite in this Doctor Who special! The Doctor and Clara face their last Christmas. Trapped on an arctic base and under attack from terrifying creatures, who are you going to call? Santa Claus!